The cluster dication [H6Ru4(C6H6)(4)](2+) revisited: the first cluster complex containing an intact dihydrogen ligand? - Süss-Fink, Georg; Plasseraud, Laurent; Maisse-Francois, Aline; Stoeckli-Evans, Helen; Berke, Heinz; Fox, Thomas; Gautier, Régis; Saillard, Jean-Yves (My University, 2000)
A low-temperature H-1-NMR study suggests the tetranuclear cluster dication [H6Ru4(C6H6)(4)](2+) (1) to contain an H-2 ligand that undergoes, upon warming of the solution, an intramolecular exchange with the four hydride ligands at the Ru-4 framework. Whereas two of the three NMR signals at - 120 degrees C in the hydride region show T-1 values in the range 200-300 ms, the least deshielded resonance at delta = - 17.33 ppm exhibits a T-1 value of only 34 ms, characteristic of an H-2 ligand. a re-examination of the single-crystal X-ray structure analysis of the chloride salt of 1 supports this interpretation by a short distance of 1.14(0.15) Angstrom between two hydrogen atoms coordinated as a PI-PI ligand in a side-on fashion to one of the triangular faces of the Ru-4 tetrahedron. The distance between one of the two hydrogen atoms of the H-2 ligand and one of the four hydride ligands is also very short [1.33(0.15) Angstrom], suggesting an additional H-2... H interaction. The presence of this H-3, unit over one of the three Ru-3 faces in 1 may explain the deformation of the Ru-4 skeleton from the expected tetrahedral symmetry. Density functional theory (DFT) calculations on 1 indicate a very soft potential energy surface associated with the respective displacement of the three interacting cofacial hydrogen atoms. In accordance with these results, the cluster dication 1 tends to loose molecular hydrogen to form the cluster dication [H4Ru4(C6H6)(4)](2+) (2). The equilibrium between 1 and 2 can be used for catalytic hydrogenation reactions. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: dihydrogen ligand; cluster; ruthenium; NMR T-1 measurements; molecular; structure; density functional calculations; MOLECULAR-HYDROGEN COMPLEXES; TRANSITION-METAL COMPLEXES; POLYHYDRIDE; COMPLEXES; RUTHENIUM COMPLEXES; AQUEOUS-SOLUTION; COORDINATION; ACTIVATION; DIHYDRIDE; HYDRIDES; APPROXIMATION